The Impact of Learning Strategies (Between Thematic and Conventional) and Cognitive Style on Learning Achievement of Third Graders Primary School - Dwi Ilham Rahardjo (Universitas Negeri Malang, 2015)
Pengaruh Strategi Pembelajaran (Tematik Versus Konvensional) dan Gaya Kognitif terhadap Prestasi Belajar Siswa Kelas III Sekolah Dasar Abstract: The objective of this study is to find out the main effect and interaction effect of variables toward the learning achievement of the third grades. Using quasy experiment, the results of the study shows: (1) there are differences in the learning achievement between the groups of the third grade students treated using thematic instructional strategies and the ones treated using conventional instructional strategies, (2) there are no differences in the learning achievement between the groups of the third grade students with the independent cognitive styles and the ones with the dependent cognitive styles, (3) there is no interaction between instructional strategies and cognitive styles on the learning achievement of the third grade elementary school students. Key Words: tematic instructional, conventional instructional, cognitive learning style, student achievement Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh strategi pembelajaran (tematik versus konvensional) dan gaya kognitif terhadap prestasi belajar, dan pengaruh interaksi antara strategi pembelajaran dan gaya kognitif terhadap prestasi belajar siswa kelas 3 Sekolah Dasar. Dengan menggunakan desain penelitian eksperimen semu, simpulan penelitian ini adalah: (1) terdapat perbedaan pengaruh  strategi pembelajaran terhadap prestasi belajar siswa, (2)  tidak ada perbedaan prestasi belajar siswa yang memiliki gaya kognitif yang berbeda, (3) tidak terdapat interaksi antara strategi pembelajaran dan gaya kognitif terhadap prestasi belajar siswa. Kata kunci: pembelajaran tematik, pembelajaran konvensional, gaya kognitif, prestasi belajar